(untitled) (Journal of Applied Learning and Teaching, 2024)
Our research article explores teachers’ perceptions of components of effective language teaching from a community of inquiry (CoI) perspective. 20 teachers completed a narrative frame, 15 of whom participated in a semi-structured interview in which they discussed the factors contributing to effective teaching. The thematic analysis of the data employing the underpinning theoretical framework of the study revealed nine sub-themes in three CoI themes. The sub-themes in the teaching presence theme were classroom dynamic and discourse, classroom and learning management, and evaluation and assessment. The emergence of meaningful learning, critical thinking, and students’ engagement was observed in cognitive presence, and learning environment, sociocultural peculiarities, and positive relationships emerged in social presence. The findings of this study may assist teachers, teacher educators, and policymakers in improving their understanding of effective teaching and its components and planning, designing, and implementing accordingly.